'A story is not a story but a conference': Story conferences and the classical studio system. (1st June 2014) - Tieber, Claus
In analyzing the script development of Grand Hotel (1932, Edmund Goulding), this article brings an insight into the workings of the classical studio system and the way screenwriting was organized and understood during this era. The protocols of story conferences that took place at MGM under the leadership of producer Irving Thalberg deliver an exhaustive picture of the whole process, from the first screen idea, to getting the rights for a novel, to the final discussions after the screening of a rough cut. The protocols deliver evidence of screenwriting as an ongoing work in progress that was done not by a single screenwriter, but by a group of film-makers, constantly discussing all elements of the production. The concerns of the participants of these conferences included more than just storytelling; they also focused on the emotional reactions of the audience and the presentation of stars. The criteria these decisions were based upon are not 'rules' of storytelling, but reasonable assumptions about the audience's reactions. Screenwriting within the studio system was not an ongoing fight between screenwriters and producers, but an ongoing discussion about every detail of a film, constituting a rather modern and democratic system of film development.